Possible cytokine biomarkers in pediatric acute appendicitis - Nikola Stankovic; Maja Surbatovic; Ivan Stanojevic; Radoje Simić; Slavisa Djuricic; Maja Milickovic; Blagoje Grujic; Djordje Savic; Vesna Milojkovic Marinovic; Miona Stankovic; Danilo Vojvodic (BMC, 2019)
Abstract Background Diagnosis of acute appendicitis (AA) and decisions about its treatment remain among the most common dilemmas of pediatric surgical teams. Monitoring of immune response may be of importance for this purpose. Our aim was to measure and analyze serum and peritoneal fluid cytokines, in children who had undergone surgery for suspected AA. Methods Prospective investigation of serum and peritoneal fluid cytokine values was performed in 127 consecutive patients. According to the pathohistological findings, patients were divided into three groups: normal/early, uncomplicated and complicated AA. Determination of cytokine concentrations for 20 different cytokines was done using a commercial flow cytometry kit: Human Inflammation 20 plex BMS 819. Results Statistically significant differences in serum cytokine values between pathohistological groups were found for IP-10, MIP-1α and IL-10. Preoperative cut-off values of IP-10, MIP-1α and IL-10 between groups were obtained using ROC curve analysis. Positive correlations between serum and peritoneal concentrations were recorded for most of the analyzed cytokines. Conclusion IP-10, MIP-1α and IL-10 showed potential in assessment of AA in children. Confirmatory studies with a larger number of patients are required to prove reliability of these biomarkers.